Nitro-Group π System Drives the Interaction of RRx-001 with Electrons in Solution - Sedmidubská, Barbora; Denisov, Sergey; Mostafavi, Mehran; Denifl, Stephan; Izadi, Fahrad; Ončák, Milan; Luxford, Thomas F M; Chvátil, David; Pinkas, Jiří; Kočišek, Jaroslav (Chemistry (Weinheim an der Bergstrasse, Germany), 2025)
Reactivity toward low-energy electrons (LEE) has been hypothesized as a cause of radio-modifying properties for various molecules. LEE's transient nature, however, prevents the establishment of clear links between initial processes at the sub-ps time scale and the final products of radiolysis. Here, such links are explored for the radio-modifying compound RRx-001 (1-bromoacetyl-3,3-dinitroazetidine). Picosecond pulse radiolysis demonstrates the high scavenging capacity of the molecule for secondary quasi-free and solvated electrons forming stable parent anions confirmed by studies of microsolvated RRx-001 in clusters. The anions decay either via auto-detachment of an electron or dissociate involving hydrogen transfer from solvent, resulting in NO2 and 1-(bromoacetyl)-3-nitroazetidine. Surprisingly, no Br dissociation is observed despite its high electron affinity. We assign this behavior to the "inaccessibility" of sigma virtual states for electrons in the solvent, which can be of a general nature.
Keywords: radiosensitizer; state selective; catalytic electron; electron attachment; low‐energy electrons